Design of a smart manufacturing system with the application of multi-access edge computing and blockchain technology - Lee, C. K. M. (2021)
Smart manufacturing is the core of the modern production and manufacturing industry as it moves towards digitalization. The successful implementation of smart manufacturing needs the support of information technology, data technology, and operational technology, among which edge computing, blockchain technology and artificial intelligence can play significant roles facilitating the development of smart manufacturing. In this research, a smart manufacturing system is proposed considering the integration of edge computing and blockchain technology. The introduction of edge computing can balance the computational workload and provide a more timely response for terminal devices. Blockchain technology can be utilized to promote both the device-level data transmission and the manufacturing service transaction. Moreover, regarding the computational task assignment in smart manufacturing systems, a mathematical model is proposed, and further solved using a swarm intelligence-based approach. Numerical experiments show that the introduction of the edge computing mechanism in smart manufacturing can significantly improve the processing time, especially with a large number of tasks.